1986
DOI: 10.1126/science.3726545
|View full text |Cite
|
Sign up to set email alerts
|

Stable Amplified DNA in Drug-Resistant Leishmania Exists as Extrachromosomal Circles

Abstract: The relative stability of amplified DNA in drug-resistant Leishmania major was previously reported to be dependent on location, that is, unstable amplified DNA was extrachromosomal and stable amplified DNA was chromosomal. Leishmanial chromosomes have now been directly examined by means of orthogonal-field-alternation gel electrophoresis (OFAGE). The amplified DNA's in three resistant cell lines displayed unusual migration and were clearly extrachromosomal, regardless of whether the amplified DNA's were stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…In contrast, a nonconservative model would require some alteration in the structure of the wild-type H-region chromosome, which was not observed. Similar data have been presented for the H-and R-region amplifications observed in certain lines of L. major (1,2,19). It is tempting to speculate that the amplification mechanism itself was conservative, perhaps occurring by a process involving localized overreplication followed by recombinations among the overreplicated DNAs.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In contrast, a nonconservative model would require some alteration in the structure of the wild-type H-region chromosome, which was not observed. Similar data have been presented for the H-and R-region amplifications observed in certain lines of L. major (1,2,19). It is tempting to speculate that the amplification mechanism itself was conservative, perhaps occurring by a process involving localized overreplication followed by recombinations among the overreplicated DNAs.…”
Section: Discussionsupporting
confidence: 61%
“…6B) exhibited the unusual mobility properties characteristic of supercoiled circular DNAs, such as pulse time-dependent mobility (relative to those of linear DNA size markers [1,19,22]). Using pulse times of 90 to 150 s, this DNA had an apparent molecular size of about 1,000 kb (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1, had apparent sizes in the range of 340 to 430 kb compared with those of the S. cerevisiae chromosomes and lambda multimers. This apparent change in sizes of bands with respect to the linear size standards and in response to pulse time variation would be expected if the DNA molecules were supercoiled circular plasmids (9,17,19). In contrast, Borrelia DNA bands in the range of 150 to 200 kb in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…These experiments indicated that megabase-sized B. burgdorferi DNA was not a supercoiled circle. Although evidence to date suggests that open circular DNA migrates through a pulsed-field gel system, such as TAFE, very slowly if at all (19,21), we addressed the possibility that megabase-sized DNA of B. burgdorferi was an open circle by using twodimensional agarose gel electrophoresis. Open circular phage A DNA served as a control; it along with linear phage A DNA were driven a short distance into the agarose gel with a constant electrical field of low voltage.…”
Section: Methodsmentioning
confidence: 99%